Efficient Wastewater Treatment via Aeration Through a Novel Nanobubble System in Sequence Batch Reactors - Ahmadi, Mehrdad; Doroodmand, Mohammad Mahdi; Nabi Bidhendi, Gholamreza; Torabian, Ali; Mehrdadi, Nasser (Frontiers in Energy Research, 2022)
The aerobic wastewater treatments depend on the aeration. Hence, size of the bubbles used in the aeration system may play a crucial role in this regard. This study attempted to investigate the effects of aeration bubbles size on wastewater treatment efficiency of a “Sequence Batch Reactor” (SBR) system at laboratory scale using a novel designed fine/nano bubble forming instrumentation system. Based on presence of microorganisms in stationary phase, chemical oxygen demand removal efficiency on fifteenth day (80.0 and 95.0%) was majorly better than 10th and 15th day in fine and nano bubble aeration systems. Moreover, with increasing sludge age, “Sludge Volumetric Index” (SVI) increased up to 170.0 mL g-1 in 15th day. In addition, sludge rate and F/M ratio were much higher and expressively less in nano bubbles system rather than fine-bubbles system at which sludge was majorly denser. Therefore, the sludge was more easily deposited and percentage of dry sludge was higher compared with the fine-bubble system. Thus, oxygen and specific oxygen uptake rate consumption was significantly reduced. The efficiency of the phosphorus removal was estimated to be between 54.0-60.0% for nano bubble aeration, compared to the general systems such as the SBR (10-20%) under similar condition. In addition, efficiency of the nitrogen removal in nano bubble aeration system with different densities of 40.0, 50.0, and 60.0 mL g-1 was found as 99.0%, relatively higher than fine bubble with 96.0 % nitrogen efficiency. As final conclusion, nano bubble aeration system could give considerably promoted efficiencies in all terms of the tested treatment effective parameters.